A review on biogas upgrading in anaerobic digestion systems treating organic solids and wastewaters via biogas recirculation. (January 2022) - Yuan, Tian; Zhang, Zhenya; Lei, Zhongfang; Shimizu, Kazuya; Lee, Duu-Jong
Graphical abstract: Highlights: Biogas recirculation as a mixing strategy in AD can contribute to biogas upgrading. Biogas recirculation increases physicochemical dissolution and fixation of CO2 . Promoted growth of hydrogenotrophic methanogen and homoacetogen consumes more CO2 . Biogas recirculation help establish a robust AD suitably treating various organics. Biogas recirculation-based AD sustainably achieves high caloric biogas production. Abstract: Biogas upgrading is an essential process for efficient and safe utilization of biogas produced from anaerobic digestion (AD), a cost-effective and environmentally friendly technology for bioenergy recovery from organic wastes. Biogas recirculation in AD reactors has been recently reported as a cost-effective and promising method to enhance methane content in biogas. This review aimed to summarize the state-of-the-art of biogas recirculation-based AD systems to better understand the possible mechanisms and main factors relating to in-situ biogas upgrading. It shows that biogas recirculation in the AD reactor can not only enhance methane content via both physicochemical and biological effects, but also help establish a robust AD system with high buffering capacity for highly efficient treatment of various organic wastes. More research works are demanding for a better understanding of the mechanisms and the optimization of the whole AD system, targeting its further development for high-calorie bioenergy production.